A new window to tidal asteroseismology: non-linearly excited stellar eigenmodes and the period spacing pattern in KOI-54. Issue 1 (20th September 2022) - Guo, Zhao; Ogilvie, Gordon I; Li, Gang; Townsend, Richard H D; Sun, Meng
ABSTRACT: We revisit the tidally excited oscillations (TEOs) in the A-type main-sequence eccentric binary KOI-54, the prototype of heartbeat stars. Although the linear tidal response of the star is a series of orbital-harmonic frequencies which are not stellar eigenfrequencies, we show that the non-linearly excited non-orbital-harmonic TEOs are eigenmodes. By carefully choosing the modes which satisfy the mode-coupling selection rules, a period spacing (Δ P ) pattern of quadrupole gravity modes (Δ P ≈ 2520–2535 s) can be discerned in the Fourier spectrum, with a detection significance level of 99.9 per cent . The inferred period spacing value agrees remarkably well with the theoretical l = 2, m = 0 g modes from a stellar model with the measured mass, radius, and effective temperature. We also find that the two largest-amplitude TEOs at N = 90, 91 harmonics are very close to resonance with l = 2, m = 0 eigenmodes, and likely come from different stars. Previous works on tidal oscillations primarily focus on the modelling of TEO amplitudes and phases, the high sensitivity of TEO amplitude to the frequency detuning (tidal forcing frequency minus the closest stellar eigenfrequency) requires extremely dense grids of stellar models and prevents us from constraining the stellar physical parameters easily. This work, however, opens the window of real tidal asteroseismology by using the eigenfrequencies of the star inferred from the non-linear TEOs and possibly very-close-to-resonance linear TEOs. Our seismic modelling of these identified eigen g-modes shows that the best-matching stellar models have ( M ≈ 2.20, 2.35 M⊙ ) and super-solar metallicity, in good agreement with previous measurements.